Interactive simulator of complex supply-chain dynamics with customer preference feedback - Perea Munoz, Lourdes; Herrero, Víctor Angel; Clausse, Alejandro (Science Alert, 2012)
Fil: Perea Munoz, Lourdes. Universidad Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina